CÓRDOBA, David; SÁEZ, Javier; VIDARTE, Paco (Eds.). Teoría queer. Políticas bolleras, maricas, trans, mestizas. - Clímaco, Danilo de Assis (Revista Estudos Feministas, 2008)
CÓRDOBA, David; SÁEZ, Javier; VIDARTE, Paco (Eds.). Teoría queer. Políticas bolleras, maricas, trans, mestizas.